Komunikasi dakwah efektif Badiuzzaman Said Nursi melalui praktis persuasif di Malaysia / Muaz Mohd Noor - Mohd Noor, Muaz (2024)
One of the noteworthy deficiencies in contemporary da'wah lies in the insufficient mastery and comprehension of effective communication approaches when disseminating Islamic teachings. This shortcoming is often compounded by a lack of proficiency in persuasive communication. Consequently, this study aims to scrutinize the communication approach employed by Badiuzzaman Said Nursi in propagating Islamic da'wah through persuasive practices. Additionally, it seeks to analyze the persuasive practices adopted by preachers in Malaysia. To ascertain this subject comprehensively, the author employed a library research method with a phenomenological design. Through an analysis of key texts from the Rasail an-Nur book collection (considered primary sources) and other pertinent secondary sources, the author elucidated Badiuzzaman Said Nursi's effective da'wah communication approach. Furthermore, qualitative data gathered from interviews with 13 informants well-versed in Rasail an-Nur were descriptively analyzed using thematic analysis. The examination of interview transcripts yielded 162 codes, 40 categories, 12 sub-themes, and 6 themes, facilitated by ATLAS.ti software version 9. The findings highlighted the efficacy of Said Nursi's communication approach, emphasizing its considerable impact on diverse segments of society. His approach encompassed both written and verbal communication, as well as non-verbal practices, all meticulously implemented. Moreover, preachers in Malaysia were found to generally employ six persuasive approaches akin to those practiced by Said Nursi, namely reciprocity, commitment & consistency, authority, scarcity, social proof, and liking. The research concludes that Badiuzzaman Said Nursi's da'wah communication approach, with its emphasis on persuasive practices, continues to yield positive outcomes, contributing to the wellbeing and advancement of Muslim communities.